Las fuentes de las "Allegoriae quaedam sanctae scripturae" ("CPL" 1190) de Isidoro de Sevilla - Martín-Iglesias, José Carlos 1968- (2018)
The Allegoriae quaedam sanctae scripturae (CPL 1190) by Isidore of Seville are one of the least studied works of the bishop of Seville. Undoubtedly, the reason for this is that they still lack a critical edition and, by extension, a good analysis of their Patristic sources.Consequently, I offer here the first exhaustive study of the authors quoted by Isidore of Seville in the exegesis of the Allegoriae and point out the similarities between a good number of passages of this work and other treatises of the same author.
Keywords: Isidoro, -- Santo, Arzobispo de Sevilla; Literatura